2020
DOI: 10.33137/twpl.v42i1.33384
|View full text |Cite
|
Sign up to set email alerts
|

Second-generation Persians’ Participation in the Oklahoma Dialect

Abstract: Vowel systems are a rich source of information about speakers’ social affiliations and linguistic influences. With the purpose of contributing to recent dialect investigations of immigrant communities inside the US, this study examined the acoustics of bilingual Persian-Oklahomans and their participation in Oklahoma dialect features. Twenty Oklahoma-born second-generation Persian-Americans were compared to ten monolingual European-Oklahomans with respect to their production of local dialect features. Results s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…Similarly, Farsi /u/ is completely distinct from the fronted English /u/ (GOOSE). Dokhtzeynal (2020) observed that the English /ae/ produced by these heritage speakers is backed and lowered compared to that of European-American Oklahoma English. This could be an effect of Farsi /ae/ on their English /ae/ or have some other reasons to it.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…Similarly, Farsi /u/ is completely distinct from the fronted English /u/ (GOOSE). Dokhtzeynal (2020) observed that the English /ae/ produced by these heritage speakers is backed and lowered compared to that of European-American Oklahoma English. This could be an effect of Farsi /ae/ on their English /ae/ or have some other reasons to it.…”
Section: Discussionmentioning
confidence: 92%
“…For the purpose of the present study, the 35% and 80% F1 and F2 values were chosen in order to check for possible glides in Farsi vowels and to check for possible effects from the participants' English diphthongs on their Farsi vowels. Measurements from participants' English vowels were taken from Dokhtzeynal (2020), who conducted a study on the English vowel system of the same Persian immigrants and Farsi heritage speakers who participated in the present study. Formant values for monolinguals were taken from Ghaffarvand Mokari et al (2017).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation